Designing Jumping Task on Percent using PMRI and Collaborative Learning - Putri, Ratu Ilma Indra; Zulkardi, Zulkardi (International Journal on Emerging Mathematics Education, 2019)
Contrast to the shared task at the beginning of mathematics lesson, jumping task is the central part of the teaching that uses higher order thinking skills (HOTs) in Japan. In Indonesia, the curriculum 2013 revised stress on how to use HOTs in the mathematics lesson, the daily life context, and collaborative learning. The goal of this research to know the characteristics of the jumping task which valid, practical and useful supporting primary school students learning percents. This research uses design research as a method. In designing the content materials and their contexts, this research uses PMRI (Indonesian version of Realistic Mathematics Education instructional theory. Moreover, in the designing and implementing learning process, this research use lesson study for learning community (LSLC). Results of this research are valid and practical jumping tasks on mathematics topic percents. Students with low performance have difficulties in solving jumping tasks. However, with collaborative learning, students can answer the percent jumping tasks.